Computer Security: 20 Things Every Employee Should Know - Rothke Ben (MC Graw Hill, 2005)
It’s five o’clock, do you know where your confidential office document is? The truth is that many employees may not. This convenient handbook brings your workplace up to speed with 21st century security issues from computer passwords to hard copy document disposal. Covers technical issues and social engineering scenarios that put corporate security and data at risk. --This text refers to an out of print or unavailable edition of this title.